Inappropriate use of the conciliation in the action under administrative law by the public servant: competence in his duty and responsibility - Martínez-Silva, Víctor Diomedes (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Conciliation is a tool that historically has been used to fix disagreements among human beings; thus, it becomes an appropriate mechanism to solve conflicts. For that reason, law uses it as an effective alternative whereby justice approaches to citizens and allows judicial system to take care of more important issues.